Quality-by-design and current good practices for the production of test and reference materials for micro- and nano-plastic research - Korinna Altmann; Lukas Wimmer; Victor Alcolea-Rodriguez; Tassilo Waniek; Volker Wachtendorf; Kay Matzdorf; Dmitri Ciornii; Petra Fengler; Frank Milczewski; Itziar Otazo-Aseguinolaza; Manuel Ferrer; Miguel A. Bañares; et al. (Journal of Hazardous Materials, 2025)

Addressing retail meat waste: A focus group study on discolored beef - Annika J. Thies; Maggie Holloway; Brianne A. Altmann; Amanda M. Countryman; Colton Smith; Mahesh N. Nair (Food and Humanity, 2025)

Consumer willingness to pay (WTP) for beef based on color and price discounts - Annika J. Thies; Brianne A. Altmann; Amanda M. Countryman; Colton Smith; Mahesh N. Nair (Meat Science, 2024)

S04-01 Inflammation-related key events stimulated by micro- and nanoplastics - A. van den Berg; K. Adriaans; E. Hoppener; L. Parker; A. Boersma; K. Altmann; J. Legler; R. Pieters (Toxicology Letters, 2024)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Does climate variability influence the demography of wild primates? Evidence from long‐term life‐history data in seven species - Fernando A. Campos; William F. Morris; Susan C. Alberts; Jeanne Altmann; Diane K. Brockman; Marina Cords; Anne Pusey; Tara S. Stoinski; Karen B. Strier; Linda M. Fedigan (Global Change Biology, 2017)
Earth's rapidly changing climate creates a growing need to understand how demographic processes in natural populations are affected by climate variability, particularly among organisms threatened by extinction. Long‐term, large‐scale, and cross‐taxon studies of vital rate variation in relation to climate variability can be particularly valuable because they can reveal environmental drivers that affect multiple species over extensive regions. Few such data exist for animals with slow life histories, particularly in the tropics, where climate variation over large‐scale space is asynchronous. As our closest relatives, nonhuman primates are especially valuable as a resource to understand the roles of climate variability and climate change in human evolutionary history. Here, we provide the first comprehensive investigation of vital rate variation in relation to climate variability among wild primates. We ask whether primates are sensitive to global changes that are universal (e.g., higher temperature, large‐scale climate oscillations) or whether they are more sensitive to global change effects that are local (e.g., more rain in some places), which would complicate predictions of how primates in general will respond to climate change. To address these questions, we use a database of long‐term life‐history data for natural populations of seven primate species that have been studied for 29–52 years to investigate associations between vital rate variation, local climate variability, and global climate oscillations. Associations between vital rates and climate variability varied among species and depended on the time windows considered, highlighting the importance of temporal scale in detection of such effects. We found strong climate signals in the fertility rates of three species. However, survival, which has a greater impact on population growth, was little affected by climate variability. Thus, we found evidence for demographic buffering of life histories, but also evidence of mechanisms by which climate change could affect the fates of wild primates.

Improved Automatic Segmentation of White Matter Hyperintensities in MRI Based on Multilevel Lesion Features - M. Rincón; E. Díaz-López; P. Selnes; K. Vegge; M. Altmann; T. Fladby; A. Bjørnerud (Neuroinformatics, 2017)

Dent and Flint maize diversity panels reveal important genetic potential for increasing biomass production - R. Rincent; S. Nicolas; S. Bouchet; T. Altmann; D. Brunel; P. Revilla; R. A. Malvar; J. Moreno-Gonzalez; L. Campo; A. E. Melchinger; W. Schipprack; E. Bauer; et al. (Theoretical and Applied Genetics, 2014)

Costs of reproduction in a long-lived female primate: injury risk and wound healing - Elizabeth A. Archie; Jeanne Altmann; Susan C. Alberts (Behavioral Ecology and Sociobiology, 2014)

When good neighbors don't need fences: temporal landscape partitioning among baboon social groups - A. Catherine Markham; Vishwesha Guttal; Susan C. Alberts; Jeanne Altmann (Behavioral Ecology and Sociobiology, 2013)

Techniques for Studying Living Primates - Stuart A. Altmann (Journal of Mammalian Evolution, 2011)

Genetic evidence reveals temporal change in hybridization patterns in a wild baboon population - J. TUNG; M. J. E. CHARPENTIER; D. A. GARFIELD; J. ALTMANN; S. C. ALBERTS (Molecular Ecology, 2008)
The process and consequences of hybridization are of interest to evolutionary biologists because of the importance of hybridization in understanding reproductive isolation, speciation, and the influence of introgression on population genetic structure. Recent studies of hybridization have been enhanced by the advent of sensitive, genetic marker‐based techniques for inferring the degree of admixture occurring within individuals. Here we present a genetic marker‐based analysis of hybridization in a large‐bodied, long‐lived mammal over multiple generations. We analysed patterns of hybridization between yellow baboons ( Papio cynocephalus ) and anubis baboons ( Papio anubis ) in a well‐studied natural population in Amboseli National Park, Kenya, using genetic samples from 450 individuals born over the last 36 years. We assigned genetic hybrid scores based on genotypes at 14 microsatellite loci using the clustering algorithm implemented in structure 2.0, and assessed the robustness of these scores by comparison to pedigree information and through simulation. The genetic hybrid scores showed generally good agreement with previous morphological assessments of hybridity, but suggest that genetic methods may be more sensitive for identification of low levels of hybridity. The results of our analysis indicate that the proportion of hybrids in the Amboseli population has grown over time, but that the average proportion of anubis ancestry within hybrids is gradually decreasing. We argue that these patterns are probably a result of both selective and nonselective processes, including differences in the timing of life‐history events for hybrid males relative to yellow baboon males, and stochasticity in long‐distance dispersal from the source anubis population into Amboseli.

Gap Junction Coupling and Apoptosis in GFSHR-17 Granulosa Cells - A. Ngezahayo; B. Altmann; M. Steffens; H.-A. Kolb (The Journal of Membrane Biology, 2005)

Regulation of Ion Fluxes, Cell Volume and Gap Junctional Coupling by cGMP in GFSHR-17 Granulosa Cells - A. Ngezahayo; B. Altmann; H. -A. Kolb (The Journal of Membrane Biology, 2003)

Phosphate acquisition heterosis in Arabidopsis thaliana: a morphological and physiological analysis - Ram A. Narang; Thomas Altmann (Plant and Soil, 2001)

The Arabidopsis PHD-finger protein SHL is required for proper development and fertility - C. Müssig; A. Kauschmann; S. D. Clouse; T. Altmann (Molecular Genetics and Genomics, 2000)

Fate and effects of micropollutants in the Gironde estuary, France: a multidisciplinary approach - C. Amiard-Triquet; S. Altmann; J. C. Amiard; C. Ballan-Dufrançais; P. Baumard; H. Budzinski; C. Crouzet; P. Garrigues; E. His; A. Y. Jeantet; R. Menasria; P. Mora; et al. (Hydrobiologia, 1998)

Human papillomavirus type 16 (HPV 16) E7 and major histocompatibility complex (MHC) class I and II expression in human keratinocytes in culture - A. Hoos; C. D'Incan; L. Gissmann; A. Altmann; F. Momburg; I. Nindl; W. Osen; BH. Schönning; I. Jochmus (Archives of Virology, 1996)

Two models for the evolution of polygyny - Stuart A. Altmann; Stephen S. Wagner; Sarah Lenington (Behavioral Ecology and Sociobiology, 1977)